In-vivo evaluation of fungicides against Lasiodiplodia theobromae infecting die back disease of mango (var. Alphanso) (Indian Journal of Arid Horticulture, 2017)
In vivo evaluation of fungicides showed Bordeaux mixture (1.0%) was found to be the most effective in controlling the  die back disease of mango after each spraying and it has given cent per cent infection control along with thiophanate methyl,  hexaconazole, propiconazole and hexaconazole + zineb. All these fungicides inhibit the growth of fungus in first and second  spraying on both the mango orchard during 2011-12 to 2012-13 respectively. The study is to promote commercial cultivation of  the mango var. alphanso by small and middle scale farmers.
Keywords: Die back; fungicides; in-vivo; Lasiodiplodia; mango